Rissoidae (Mollusca, Gastropoda, Rissooidea) from taphocoenotic assemblages of the Strait of Sicily (Mediterranean Sea) with the description of two new species - Amati, Bruno; Taviani, Marco; Oliverio, Marco (Zootaxa, 2024)
Twenty-one rissoid species have been found in four bathyal samples from the Strait of Sicily, represented exclusively by empty shells. Some of these species are shallow water dwellers, associated with algal facies, others are typical of deep-sea (bathyal-abyssal). Two species are described as new (Alvania ismar n. sp. and Manzonia schmidti n. sp., both of probable Plio-Pleistocene age) and two have not been identified at the species level, due to the small number of specimens found and their poor state of conservation. Taxonomical remarks on some taxa are provided.